FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA JURUSAN AKUNTANSI UNTUK BERKARIR DIBIDANG PERPAJAKAN (Studi Empiris pada Universitas Riau, UIN Sultan Syarif Kasim, Universitas Islam Riau, dan Universitas Lancang Kuning) - Putri, Rahmalia Prima; -, Zirman; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze and gets empirical prove of perception, motivation, financial awards, professional recognition, and labour market concideration toaccounting students’ interest in taxation field. Respondents in this researchis accounting students fromRiau University, Islamic State University Sultan Syarif Kasim, Riau Islamic University and Lancang Kuning University. The sampling is selected using purposive sampling,data collection method using a questionnaire with the number of sample of this research was 260 students. This research is a quantitative model with data analysis methods includevalidity, reliability, normality test, classical assumptions: heteroscedasticity and multicollinearity, test determinant coefficient and hypothesis test: t test using SPSS software version 20 to process data. The results of this research indicate that perception, financial awards, and professional recognition influence accounting students’ interest in taxation field. Other while, motivation and labour market concideration have no influence accounting students’ interest in taxation field.Keywords: perception, motivation, financial awards, professional recognition, labour market concideration, accounting students’ interest in taxation field.